2015
DOI: 10.1016/j.jab.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of miRNAs targeting the key nuclear receptors regulating CYP3A4 gene expression: The challenge of the CYP3A4 "missing heritability" enigma

Abstract: Cytochrome P450Metabolism a b s t r a c tThe expression of the main cytochrome P450 enzyme CYP3A4 displays enormous interindividual variability. Studies addressing the genetic variability of either the CYP3A4 gene itself or its key transcription factors have not found any crucial polymorphism contributing to this variability in expression, a phenomenon is referred to as the ''missing heritability of CYP3A4 variability.'' Several reports have recently described microRNAs (miRNAs) targeting the CYP3A4 gene and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We focused on the family of glutathione peroxidases, and indeed confirmed that all GPxs were predicted to be a target of many miRNAs ( Table 1 and Table S1 ). The number of unique miRNas correlates well with the 3′UTR length of each individual GPxs ( Figure 1 ) [ 143 ]. As previously reported, shorter 3′UTR are more common for housekeeping genes [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the family of glutathione peroxidases, and indeed confirmed that all GPxs were predicted to be a target of many miRNAs ( Table 1 and Table S1 ). The number of unique miRNas correlates well with the 3′UTR length of each individual GPxs ( Figure 1 ) [ 143 ]. As previously reported, shorter 3′UTR are more common for housekeeping genes [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the extended study of 136 human liver samples, significant correlation (r 2 ¼ 0.53) between OCT1 protein and transcript levels was observed, suggesting low post-transcriptional regulation of SLC22A1 gene expression (Nies et al, 2009). The short 3-UTR of OCT1 mRNA provides probably limited potential for miRNAs regulation, as evident from the correlation between length of 3-UTR of mRNAs and the number of regulatory miRNAs predicted by in silico methods (Ramamoorthy & Skaar, 2011;Smutny et al, 2015). On the other hand, using miRDB database (ver.…”
Section: Involvement Of Mirnas In Oct1 Regulationmentioning
confidence: 99%